Pengaruh Pengalaman Pelanggan, Kualitas Layanan, dan Promosi terhadap Keputusan Penggunaan Aplikasi OVO pada Mahasiswa Uniska Kediri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine and explain the influence of customer experience, service quality, and promotion on the decision to use the OVO application among Uniska Kediri students. The research applied a probability sampling method using a saturated sample approach for an unknown population, calculated through the Hair formula, and obtained 114 respondents. The data were analyzed using several statistical tests, including validity, reliability, normality, multicollinearity, heteroscedasticity, linearity, and determination (R²), processed through SPSS version 25.The research findings show that the customer experience variable does not have a significant effect on the decision to use the OVO application, with a significance value of 0.380 > 0.05 and a t-count of 0.882 < t-table of 1.981. Similarly, the service quality variable also does not significantly affect the decision to use, with a significance value of 0.833 > 0.05 and a t-count of 0.211 < t-table of 1.981. In contrast, the promotion variable has a significant positive effect on the decision to use the OVO application, with a significance value of 0.001 < 0.05 and a t-count of 3.287 > t-table of 1.981. Simultaneously, customer experience, service quality, and promotion collectively have a significant influence, with a significance value of 0.000 < 0.05 and an F-count of 6.883 > F-table of 2.69. The R² value reflects the combined effect of these variables on user decisions.